Densification and microstructural evolution of bulk Al2O3–Y3Al5O12(YAG) eutectic ceramic fabricated by spark plasma sintering. Issue 9 (15th June 2019) - Zhao, Di; Su, Haijun; Liu, Haifang; Liu, Yuan; Shen, Zhonglin; Yao, Bin; Guo, Min; Guo, Yueling; Zhang, Jun; Liu, Lin; Fu, Hengzhi
Abstract: Highly dense Al2 O3 Y3 Al5 O12 (YAG) eutectic bulk ceramics are successfully prepared by spark plasma sintering (SPS) using fine ceramic particles with homogeneous eutectic structure. The fine ceramic particles are obtained by pulverizing the eutectic ceramic rods prepared with laser floating zone melting (LFZM). The densification and microstructural evolution of eutectic ceramic particles during SPS are investigated. The results show that the sintering process can be divided into four stages, and densification is mainly accomplished with a short time in the stage of 1450–1580 °C. High-temperature diffusions on grain surface and in lattice or grain boundary of fine particles are primary densification mechanisms. Three types of microstructural evolutions during sintering are revealed, in which large eutectic particles mainly consolidate with an indirect way due to fine particles between them. On the basis, the effects of sintering temperature on microstructure and mechanical properties are discussed. The results pave a feasible way to prepare bulk eutectic ceramics with enhanced toughness by sintering method.